A construction company can remove 3/4 tons of dirt from a construction site each hour. how long will it take them to remove 36 tons of dirt from the site? (Answer needs to be in simplest form)

Answers

Answer 1
Answer:

It will take the construction company 48 hours to remove 36 tons of dirt from the site.The construction company can remove \( \frac{3}{4} \) tons of dirt from the site each hour.

To find out how long it will take them to remove 36 tons of dirt, we can set up a proportion

\(\frac{\text{Amount of dirt removed}}{\text{Time}} = \frac{\text{Amount of dirt removed}}{\text{Time}}\)

Given:Amount of dirt removed in one hour = \( (3)/(4) \) tons

Total amount of dirt to be removed = 36 tons

Let  t  represent the time in hours it will take to remove 36 tons of dirt. Plugging in the values:\(((3)/(4))/(1) = (36)/(t)\)

Solving for \( t \): \(t = (36)/((3)/(4)) = (36 * 4)/(3) = 48\)hours

So, it will take the construction company 48 hours to remove 36 tons of dirt from the site.

To know more about construction:

brainly.com/question/33434682

#SPJ3

Answer 2
Answer:

Answer:

48hours

Step-by-step explanation:

36÷(3/4)

36*(4/3)

144/3

48


Related Questions

Solve the inequality 5y + 4 < 3y + 17
$641.29 is what percent of $986,60? I need this ASAP
Here's a graph of a linear function. Write the equation that describes that function.
Rachel wants to purchase a new I-Tablet on Black Friday for $450. Better Buy offers twoinstallment plans for purchasing this item.Plan A: a fixed weekly payment of $25Plan B: a $120 initial payment, followed by weekly payments of $5After 12 weeks, how much money would Rachel spend on each plan?A Plan A: $300; Plan B: $60B Plan A: $300; Plan B: $180C Plan B: $300; Plan A: $60D Plan B: $300; Plan A: $180
How many units away is 1 from -6 on a number line?-7-557

Olve the system of equations below.3x+4y=10
6x-2y=40

(6,-2)

(2,6)

(2,-6)

(-2,-6)

Answers

Answer:

The correct solutions are (6, -2).

Step-by-step explanation:

For the first equation, rearrange to make x the subject.

3x + 4y = 10

3x = 10 -4y

Divide the whole equation by 3 to isolate x:

3x = 10 -4y\n3x / 3 = (10)/(3) - (4)/(3)y\nx = (10)/(3) - (4)/(3)y\n

Now substitute this into the second equation:

6x - 2y = 40\n6((10)/(3) - (4)/(3)y) - 2y = 40\n6((10)/(3)) + 6((4)/(3))  - 2y = 40

20 - 8y - 2y = 40\n20 - 10y = 40

Subtract 20 from both sides:

20 - 10y = 40

20 - 10y - 20 = 40 - 20

-10y = 20

Divide both sides by 2:

-10y ÷ 10 = 20 ÷ 10

-y = 2 ∴ y = -2

Plug this value back into the first equation:

3x + 4y = 10

3x + 4(-2) = 10

3x + (-8) = 10

3x - 8 = 10

Add 8 to both sides:

3x - 8 + 8 = 10 + 8

3x = 18

Divide both sides by 3:

3x ÷ 3 = 18 ÷ 3

x = 6

Therefore, the correct solutions are (6, -2).

Hope this helps!

Use natural logarithmics to solve the equation round to the nearest thousandth 3e^2x +5=26

Answers

Answer:

x = 0.973

Step-by-step explanation:

3e^(2x) +5 = 26

3e^(2x) = 21 . . . . . subtract 5

e^(2x) = 7 . . . . . . . divide by 3

2x = ln(7) . . . . . . . .take the natural log

x = ln(7)/2 ≈ 0.973 . . . . divide by 2 and evaluate

Answer:

x= .973

Step-by-step explanation:

3e^2x +5=26

Subtract 5 from each side

3e^2x +5-5=26-5

3e^2x =21

Divide by 3 on each side

3/3e^2x =21/3

e^2x =7

Take the natural log on both sides

ln (e^2x) =ln (7)

2x = ln (7)

Divide by 2

2x/2 = ln(7)/2

x = ln(7)/2

x is approximately .972955075

Rounding to the nearest thousandth

x = .973

Mort is trying to save money to get out of student debt he saves money each month from his paycheck the function below relates money saved x in thousands of dollars to mouth since graduation, y.y=3x-7
identifying the slope and intercept and describe what each mean in the context​

Answers

Answer:

hello your answer is 21  y=21

Step-by-step explanation:

3 times -7 is 21- hope i helped

Solve the equation. And write all solutions in general form.

Answers

Answer:

x = pi/2 + 2 pi n                            x = pi + 2 pi n   where n is an integer

x = 5pi /3 + 2 pi n                      

Step-by-step explanation:

8 cos^2 x + 4 cos x-4 = 0

Divide by 4

2 cos^2 x +  cos x-1 = 0

Let u = cos x

2 u^2 +u -1 =0

Factor

(2u -1) ( u+1) = 0

Using the zero product property

2u-1 =0    u+1 =0

u = 1/2      u = -1

Substitute cosx for u

cos x = 1/2    cos x = -1

Take the inverse cos on each side

cos ^-1(cos x) = cos ^-1(1/2)   cos ^-1( cos x) =cos ^-1( -1)

x = pi/2 + 2 pi n                            x = pi + 2 pi n   where n is an integer

x = 5pi /3 + 2 pi n                      

Solve for the unknown.a) sin (x – 5°) = cos (35°)


b) sin (2x – 17°) = cos (x – 4°)


c) sin (x)= cos (x)


Show steps

Answers

Step-by-step explanation:

Use shifts to write sine and cosine in terms of each other.

a) sin (x – 5°) = cos (35°)

sin (x – 5°) = sin (90° – 35°)

sin (x – 5°) = sin (55°)

x – 5° = 55°

x = 60°

b) sin (2x – 17°) = cos (x – 4°)

sin (2x – 17°) = sin (90° – (x – 4°))

sin (2x – 17°) = sin (90° – x + 4°)

sin (2x – 17°) = sin (94° – x)

2x – 17° = 94° – x

3x = 111°

x = 37°

c) sin (x) = cos (x)

sin (x) = sin (90° – x)

x = 90° – x

2x = 90°

x = 45°

Factor the trinomial.
The factors of m2 + 12m + 35

Answers

Answer:

(m + 7)(m + 5)

Step-by-step explanation:

Factor, find factors of m² & 35 that, when combined, will give 12m:

m² + 12m + 35

m                 7

m                 5

(m + 7)(m + 5) is your answer.

Check: Use the FOIL method to check.

(m)(m) = m²

(m)(5) = 5m

(7)(m) = 7m

(7)(5) = 35

Combine like terms:

m² + (5m + 7m) + 35 = m² + 12m + 35 √.

Answer:

(m+7) and (m+5)

Step-by-step explanation:

Just had this on a test